Health and wellbeing of Nepalese migrant workers in Gulf Cooperation Council (GCC) countries: A mixed-methods study - Priyamvada Paudyal; Sharada Prasad Wasti; Pimala Neupane; Kavian Kulasabanathan; Ram Chandra Silwal; Ram Sharan Pathak; Anjum Memon; Carol Watts; Jiblal Sapkota; Sudip Ale Magar; Jackie Cassell (Elsevier, 2023)
Introduction: Migrant workers support low- and middle-income economies through remittances, often bearing considerable health risks with long-term consequences. This study aims to understand the health and wellbeing issues of Nepalese migrant workers in Gulf Cooperation Council (GCC) countries, a major destination for low-skilled Nepalese workers. Methodology: We conducted a mixed-methods study in Dhading district of Nepal. A pilot survey was carried out with returnee migrants from GCC countries to understand key health and wellbeing issues faced by workers. In addition, in-depth interviews were conducted with a subset of these returnee migrants and their families, and related stakeholders. These aimed to understand broader societal and policy implications in relation to labour migration. Quantitative data from the survey were analysed using descriptive statistics and thematic analysis was used for qualitative interviews. Results: 60 returnee migrants (58 males, 2 females) took part in the survey (response rate, 100%). Median age of the survey participants was 34 (IQR, 9) years and 68% had completed school level education. Returnee migrants reported suffering from various physical and mental health issues during their stay in GCC countries including cold/fever (42%), mental health problems (25%) and verbal abuse (35%). 20 participants took part in the qualitative study:10 returnee migrants (8 males, 2 females), four family members (female spouses) and six key stakeholders working in organizations related to international migration. Interview participants reported severe weather conditions resulting in physical health problems (e.g. pneumonia, dehydration and kidney disease) as well as mental health issues (including anxiety, loneliness and depression). Participants raised concerns about the usefulness and appropriateness of pre-departure training, and the authenticity of medical tests and reports in Nepal. Female migrants reported facing stigma after returning home from abroad. Language difficulties, alongside issues related to payment, insurance and support at work were cited as barriers to accessing healthcare in destination countries. Conclusion: Our study shows that Nepalese migrant workers experience severe weather conditions and suffer from various physical and mental health issues, including workplace abuse and exploitation. The study highlights an urgent need for strategies to enforce compulsory relevant pre-departure orientation and appropriate medical screening in Nepal, and fair employment terms and full health insurance coverage in destination countries. Greater collaboration between the Nepalese government and GCC countries is needed to ensure necessary legislation and regulatory frameworks are in place to safeguard the health and wellbeing of migrant workers.